Principal Conflict Management Strategies in Building a Harmonious School Environment - Herman Herman; Luluk Zahrotul Hikmah; Muharrir Muharrir; Marlinda Marlinda (ISTIFHAM, 2026)
In any organization, including schools, conflicts between school principals and administrators are inevitable. However, effective conflict management is crucial for fostering positive communication, collaboration, and trust among leaders and administrators within the school environment. This study aims to analyze conflict management strategies employed by school principals to create a harmonious school environment. Using a qualitative research approach and a literature review, the study examines relevant prior studies. The research process involves data collection, source assessment, data analysis, and manuscript compilation. The study’s findings reveal the importance of implementing conflict management policies, procedures, and training programs. These include anti-conflict policies, open communication policies, student-parent involvement policies, conflict resolution procedures, conflict reporting procedures, and evaluation and follow-up procedures. Additionally, conflict management, effective communication, and counseling training are essential for building a harmonious school environment. The practical contribution of this research lies in enhancing the capacity of school principals in conflict management practices by providing valuable information on conflict management strategies. The theoretical contribution is the development of a more comprehensive theory of conflict management for school principals, thereby contributing to a harmonious school environment.